Taken 2 [videorecording (DVD)] - Besson, Luc; Kamen, Robert Mark; Neeson, Liam; Grace, Maggie, 1983-; Janssen, Famke, 1964-; Orser, Leland; Gries, Jon, 1957-; Sweeney, D. B. (Daniel Bernard), 1961-; Grimes, Luke, 1984-; Šerbedžija, Rade, 1946-; Lacourbas, Romain; Méchaly, Nathaniel, 1972- (Twentieth Century Fox Home Entertainment, 2013)
Liam Neeson returns as Bryan Mills, an ex-CIA operative who finds himself taken hostage along with his wife. To survive, Bryan must enlist the help of an unlikely ally and use his brutally efficient skills to take out his kidnappers.